Intimate Partner Violence and Utilization of Prenatal Care in the United States. (March 2014) - Cha, Susan; Masho, Saba W.
Over 1.5 million women are victims of physical, sexual, and emotional abuse by former or present intimate partners. Intimate partner violence (IPV) around pregnancy can lead to devastating health consequences to mothers and infants. While some research suggests that IPV negatively affects the utilization of health services like prenatal care (PNC), inconsistencies in the assessment of PNC utilization, timing of partner violence, and definitions of IPV yield conflicting results. The objective for the present study is to evaluate whether preconception IPV, prenatal IPV, or IPV in the preconception and/or prenatal period affects PNC utilization. This study analyzed the 2004-2008 national Pregnancy Risk Assessment Monitoring System (PRAMS), which included 202, 367 women who delivered a live birth in the United States. IPV victimization was measured using four items that addressed physical abuse by a current or former husband/partner in the 12 months before (preconception) and during (prenatal) pregnancy. Responses were categorized as preconception, prenatal, and preconception and/or prenatal IPV. The outcome was PNC adequacy categorized as inadequate, intermediate, adequate, and adequate plus based on the Adequacy of Prenatal Care Utilization index. Separate logistic regression models provided crude and adjusted odds ratios and 95% confidence intervals (CI). Over 6% of women reported preconception and/or prenatal IPV and 26% had less than adequate PNC. Women who reported abuse before and/or during pregnancy were more likely to have inadequate PNC (odds ratio [OR] = 1.4, 95% CI = [1.3, 1.6]). Similarly, women who experienced preconception or prenatal IPV were 30% more likely to have inadequate PNC (OR = 1.3, 95% CI = [1.2, 1.5]; OR = 1.3, 95% CI = [1.1, 1.7], respectively). Adequate PNC is essential in improving pregnancy outcomes; however, women in abusive relationships may face ongoing challenges and difficulties with obtaining appropriate care. Findings underscore a critical problem and health providers are urged to screen and educate women about IPV during all preconception and prenatal visits.